2023
DOI: 10.1186/s10194-023-01645-7
|View full text |Cite
|
Sign up to set email alerts
|

Advanced brain MRI may help understand the link between migraine and multiple sclerosis

Susie Y. Huang,
Marc Salomon,
Katharina Eikermann-Haerter

Abstract: Background There is a clinical association between migraine and multiple sclerosis. Main body Migraine and MS patients share similar demographics, with the highest incidence among young, female and otherwise healthy patients. The same hormonal constellations/changes trigger disease exacerbation in both entities. Migraine prevalence is increased in MS patients, which is further enhanced by disease-modifying treatment. Clinical data show that onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…In the early stage of neurodegeneration driven by astrocytes and macrophages/microglia, the inflammatory response of CD4 + Th17 cells, CD4 + Th1 cells, IFN-γ, IL-12, TNF-α, and NO led to axon injury and demyelination ( 17 ). In addition, magnetic resonance examination of the skull in clinical studies showed that several migraine sufferers had leukoencephalopathy, which shared the neuroinflammatory mechanism with neurodegenerative diseases such as multiple sclerosis ( 18 ). While, serum IL-12p70 concentration was significantly different between children with pediatric migraine and those with encephalitis and headache, suggesting that IL-12P70 played a more important role in the mechanism related to neuroinflammation of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of neurodegeneration driven by astrocytes and macrophages/microglia, the inflammatory response of CD4 + Th17 cells, CD4 + Th1 cells, IFN-γ, IL-12, TNF-α, and NO led to axon injury and demyelination ( 17 ). In addition, magnetic resonance examination of the skull in clinical studies showed that several migraine sufferers had leukoencephalopathy, which shared the neuroinflammatory mechanism with neurodegenerative diseases such as multiple sclerosis ( 18 ). While, serum IL-12p70 concentration was significantly different between children with pediatric migraine and those with encephalitis and headache, suggesting that IL-12P70 played a more important role in the mechanism related to neuroinflammation of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions may be correlated with the presence of small lesions in the cortical or midbrain [45]. Brain imaging studies show similar white matter abnormalities in patients with MS and migraine [46]. A disturbance in the antioxidant system of the body may be a contributing factor in the coexistence of MS and migraine [47].…”
Section: Headache Types In Ms 61 Migraine Headachementioning
confidence: 97%